In-situ investigation of the impact of spreading on matrix-fracture interactions during three-phase flow in fractured porous media. (September 2019) - Sabti, Mohammad J.; Alizadeh, Amir H.; Piri, Mohammad
Highlights: Comparison of the micro-CT images obtained under the spreading and nonspreading conditions allowed us to gain a significantly improved understanding of the governing displacement physics and the matrix-fracture interactions in fractured rocks. During secondary gas injection under the spreading condition, the oil spread and formed thick and stable layers between brine and gas. These spreading layers were present not only in the matrix pores but also in the fracture conduit. The oil phase in the matrix established a hydraulic connectivity through the connected and stable spreading layers with the oil in the fracture, thereby allowing the oil in the matrix to drain into the fracture, which resulted in higher oil recovery. However, infrequent oil layers observed under nonspreading condition were not stable and collapsed easily as capillary pressure was increased during gas injection. This meant that oil had poor connectivity that hindered oil movement from the matrix to the fracture, leading to lower oil recovery compared to that of the spreading system. Abstract: This paper presents the results of a detailed experimental study performed to examine fluid flow in a water-wet fractured sandstone rock. Using high-resolution X-ray micro computed tomography technique, we systematically investigate the pore-scale displacement mechanisms and governing interactions between the matrix and fracture during gas injection. We perform two sets of flow experiments using brine/Soltrol 170 (spreading oil)/nitrogen and brine/decalin (nonspreading oil)/nitrogen fluid systems to probe the possible beneficial role of spreading phenomena in transferring oil from the matrix to the fracture during gas injection. Gas injection after primary oil drainage was used to generate a wide range of oil saturations and pore fluid arrangements with both fluid systems. Direct visualization of the pore fluid occupancies at different oil saturations in the medium reveals the significant role that the spreading oil layers play in maintaining the hydraulic conductivity of the oil phase between the matrix and the fracture. This mainly takes place at low remaining oil saturations under the spreading condition where layer drainage, in the presence of stable and connected spreading oil layers, is the dominant displacement mechanism. In the case of high remaining oil saturations, it is observed that the oil movement is primarily governed by piston-like displacements as well as the ability of the gas phase to access the pore elements adjacent to the fracture. Under the nonspreading condition, oil cannot maintain its connectivity due to the absence of the spreading layers, leading to higher residual oil saturations in the matrix and lower ultimate oil recovery.